PENGGUNAAN LEARNINGAPPS.ORG DENGAN METODE QUESTION ANSWER RELATIONSHIP DALAM PEMBELAJARAN MEMBACA PEMAHAMAN BAHASA JERMAN - Windy Sofytia Safitri, - (2023)
However, understanding a text remains to be an obstacle in Learning German for the lack of vocabulary and limited teaching materials which result in difficulties in reading long texts and answering questions. To overcome these, the researcher formulated the study with the title "Using Learningapps.org with the Question Answer Relationship method in learning German Reading Comprehension". This study was aimed to find out: 1) Student's reading comprehension skills before implementing Learningapps.org using the Question Answer Relationship method, 2) Student's reading comprehension skills after implementing Learningapps.org using the Question Answer Relationship method, 3) The effectiveness of using Learningapps.org with the Question Answer Relationship method in student's reading comprehension learning. This study employed a quasi-experimental quantitative approach. The study population included all students of X classes (10th grade) in SMAN 4 Cimahi academic year of 2022/2023 and the research sample consisted of X IPA 5 (experimental class) and X IPA 6 (control class). The results have found that: 1). The scores of the students in the experimental and control classes before the treatment were in the moderate category, 2) After the treatment, the scores of the experimental class students were in the very good category, while the control class was in the good category, 3) According to the results of the Independent Sample t-test, the use of Learningapps.org with the Question Answer Relationship method has proven to be effective as evidenced by a significance value (2-tailed) of less than 0.05, which was 0.000. Therefore, the use of Learningapps.org with the Question Answer Relationship method can be recommended as alternative learning media in learning German reading comprehension. Keywords: Learningapps.org, Learning Media, Question Answer Relationship Method.